1977
DOI: 10.1159/000180900
|View full text |Cite
|
Sign up to set email alerts
|

Acceleration of Peritoneal Dialysis with Simple Device

Abstract: Peritoneal dialysis in acute and chronic renal failure has been greatly facilitated by the advent of Tenckhoff indwelling peritoneal catheters and by strict control of peritoneal infections. A number of reports on long-term treatment have been published. A simple device has been developed and tested for regular peritoneal dialysis in the hospital and in the home, in order to accelerate the time required. Employing a ‘single needle apparatus’, a rotary pump and a thermostatic heating unit, it is possible to car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

1981
1981
1985
1985

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 7 publications
1
4
0
Order By: Relevance
“…The same directional change of ultrafiltration and solute transport indicate a simple effect on peritoneal surface rather than a complex intramembranous alteration found in many conditions [19]. In addition, the results of different techniques used to stir the stagnant dialysate fluid layers in other studies [20,21] were the same as in this study. The stable protein loss in this experiment can be explained by the fact that proteins are charged molecules of large molecular weight with high reflection coefficient and hardly influences by dialysate composition [22].…”
Section: Discussionsupporting
confidence: 75%
“…The same directional change of ultrafiltration and solute transport indicate a simple effect on peritoneal surface rather than a complex intramembranous alteration found in many conditions [19]. In addition, the results of different techniques used to stir the stagnant dialysate fluid layers in other studies [20,21] were the same as in this study. The stable protein loss in this experiment can be explained by the fact that proteins are charged molecules of large molecular weight with high reflection coefficient and hardly influences by dialysate composition [22].…”
Section: Discussionsupporting
confidence: 75%
“…It is clear from the observations that our method of semicontinuous rapid flow, high volume ex change peritoneal dialysis is superior to the methods used by Tenckhoff et al [1965] and Paolo et al [1977] as shown in table V.…”
Section: Discussionmentioning
confidence: 59%
“…In the study of Paolo et al [1977] on rapid flow peri toneal dialysis, peritoneal clearance of urea and creatinine at 6 litres/hour was 34.0 + 3 and 22.0±3.00 ml/minute, respectively. But these values are significantly lower than the values obtained in our study.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations